Analysis of the bicycle change strategy for hilly time-trials (2018)
(Eng) The uphill time-trial is a cycling race in which there is at least one mountain pass or a combination of low and high gradient sections. Usually, climbing cyclists achieve good results in uphill time-trials; however, in addition to the cyclist’s ability, the race strategy is also important for achieving good results. As part of the race strategy, the selection of the type of bicycle is important. The time-trial bicycles usually reduce aerodynamic drag while the traditional road bicycles are lighter. Taking into account the road gradient profile of the race, as part of the bicycle selection strategy, the cyclist can change the type of bicycle during the race to take advantage of each one in specific sections of the route. This paper presents a methodology for planning the bicycle change strategy for some ideal routes with simplified road gradient profiles. An optimization problem is stated to minimize the race time and to find the location on the route where the bicycle change must be done. The methodology is applied to three simplified road profiles to define if the bicycle change strategy is beneficial when different cyclist’ power output levels are analyzed.